2020
DOI: 10.1101/2020.01.10.901447
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The relationship between the waiting time of postoperative radiotherapy and the prognosis of high grade glioma:a systemic review and meta-analysis

Abstract: Objective:The relationship between the waiting time of postoperative radiotherapy and the prognosis of patients with high-grade glioma is still inconclusive, and we addressed this issue through a systematic review and meta-analysis.Methods:Twenty studies published between 1975 and 2019 about waiting times (WT) of radiotherapy with high-grade glioma were retrieved for meta-analysis.The meta-analysis was performed by converting the effect sizes of different WT into regression coefficients (β) and standard error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…According to a recent meta-analysis, the effect of radiotherapy wait time on survival in patients with glioblastoma is still controversial (28); this is difficult to verify in the present study, as the majority of patients started radiotherapy only after six weeks of surgery, which can be explained by the long waiting time due to the lack of treatment facilities. The results of our study indicated that geographical origin is a predictor of overall survival, with better overall survival observed in rural patients compared to urban patients, which might be explained by the environmental factors of patients from rural areas; future studies will be necessary to confirm and deepen these findings.…”
Section: Discussionmentioning
confidence: 68%
“…According to a recent meta-analysis, the effect of radiotherapy wait time on survival in patients with glioblastoma is still controversial (28); this is difficult to verify in the present study, as the majority of patients started radiotherapy only after six weeks of surgery, which can be explained by the long waiting time due to the lack of treatment facilities. The results of our study indicated that geographical origin is a predictor of overall survival, with better overall survival observed in rural patients compared to urban patients, which might be explained by the environmental factors of patients from rural areas; future studies will be necessary to confirm and deepen these findings.…”
Section: Discussionmentioning
confidence: 68%